The prevalence of hypertension among obese pregnant women at maternity unit husm and its associated factors - Nur Lalla, Omar (2008)
Objective: To determine the prevalence of hypertension among obese pregnant women and its associated factors at HUSM. Design Cross sectional and Cohort study for 13 months from July 2006 until July 2007. Setting : Antenatal Ward and Labour Room, Department Of Obstetrics and Gynecology, Hospital Universiti Sains Malaysia Participants : 388 participants involved in the study Methodology : Pregnant women with body mass index of ;::: 30 kg/m2 who were admitted for delivery were chosen, based on inclusion and exclusion criteria. They were being interviewed through questionnaires and the outcome of pregnancy to mothers and babies were analyzed. Main Outcome measure : Information from antenatal cards, observations on physical examinations in wards , responses from questionnaires and outcomes of pregnancy to mothers and babies. The prevalence of hypertension among obese pregnant women was 35%. Factors that contributed to the hypertension on the study groups were family history of hypertension (p= 0.026), unhealthy lifestyle practice (p <0.001 ). previous history of hypertension in pregnancy (p <0.001) and having gestational diabetes mellitus (p = 0.002). Results of the associated factors for obese hypertension by multiple logistic regression for healthy lifestyle (p < 0.001) • previous hypertension (p < 0.001) and gestational diabetes mellitus (p = , 0.003). Results showed that there was an increase in maternal outcome of Induction of Labour, IOL and premature delivery among obese hypertension women (p < 0.001). About 21.43% of the subjects who had IOL were due to preeclampsia and 31.25% were due to diabetes mellitus on treatment. There was no significant difference in the mode of delivery among these two groups with the p value of 0.398. However perinatal outcome had shown a significant result of low birth weight and admission to Neonatal Intensive Care Unit, NICU amongst obese hypertension, having the same p value of 0.001. Low Apgar score result was noted in hypertensive mothers with (p = 0.008). There was statistical significance in association between the level of uric acid and time of delivery (p = 0.001). Conclusion The percentage of prevalent hypertension among obese pregnant women was 35%. There were associated factors that contributed to hypertension such as family history of hypertension, unhealthy lifestyle practice, previous history of hypertension and having gestational diabetes mellitus. In perinatal outcome, there was also an increased incidence in low birth weight, low Apgar score and admission to NICU in hypertensive cases. This study showed statistical significance in association between the level of uric acid and time of delivery